2020
DOI: 10.1002/bjs5.50255
|View full text |Cite
|
Sign up to set email alerts
|

Availability, procurement, training, usage, maintenance and complications of electrosurgical units and laparoscopic equipment in 12 African countries

Abstract: Background Strategies are needed to increase the availability of surgical equipment in low‐ and middle‐income countries (LMICs). This study was undertaken to explore the current availability, procurement, training, usage, maintenance and complications encountered during use of electrosurgical units (ESUs) and laparoscopic equipment. Methods A survey was conducted among surgeons attending the annual meeting of the College of Surgeons of East, Central and Southern Africa (COSECSA) in December 2017 and the annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Shortage of medical equipment increases workload, relocation, washing and disinfection, depreciation, and the need for repairs. In this regard, Salah et al (13)(14)(15) found that the cost of maintaining medical equipment was directly related to their availability. Many studies found that poor low-income countries generally face a shortage of medical equipment.…”
Section: Equipment Repair Agencies and Companiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Shortage of medical equipment increases workload, relocation, washing and disinfection, depreciation, and the need for repairs. In this regard, Salah et al (13)(14)(15) found that the cost of maintaining medical equipment was directly related to their availability. Many studies found that poor low-income countries generally face a shortage of medical equipment.…”
Section: Equipment Repair Agencies and Companiesmentioning
confidence: 99%
“…[ DOI: 10.18502/jebhpme.v6i3.10854 ] [ Downloaded from jebhpme.ssu.ac.ir on 2022-[10][11][12][13][14][15][16][17][18][19][20][21][22][23] …”
mentioning
confidence: 99%
“…Laparoscopic surgery is associated with multiple barriers to implementation in LMICs. Previously, these have been described as a lack of reliable gas supply, lack of ability to maintain laparoscopic equipment, costs, irregular power supplies, lack of trained personnel, and a lack of motivation from both healthcare providers and the population [7][8][9]. However, many laparoscopic programs have been initiated despite these challenges, and innovative methods have been used to overcome many of the issues.…”
Section: Introductionmentioning
confidence: 99%
“…This creates an inequality gap, with patients undergoing laparoscopy surgery in HICs benefiting from lower infection rates [ 2 , 3 ] and better outcomes [ 4 ] compared to those undergoing open surgery. The main challenges to the introduction of laparoscopy in LMICs are the limited carbon dioxide supply for insufflation, cost and access to laparoscopic equipment, limited anaesthetic cover, and training opportunities [ 5 , 6 ]. Despite these challenges, a few laparoscopic training programmes have been successfully undertaken in Mongolia [ 7 ], Botswana [ 8 ] and South America [ 9 ], proving that it is possible provided resources are available for training and capacity building.…”
Section: Introductionmentioning
confidence: 99%